2004
DOI: 10.1007/bf03018768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phonomyography with balloon pressure mechanomyography to measure contractile force at the corrugator supercilii muscle

Abstract: P Pu ur rp po os se e: : Phonomyography is based on the creation of low frequency sounds during muscle contraction, which can be recorded and used for neuromuscular monitoring. In this study, balloon pressure mechanomyography, a novel method to measure the force of contraction via pressure changes in an air-filled balloon, was compared with phonomyography to determine neuromuscular blockade at the corrugator supercilii muscle. M Me et th ho od d: :After approval of the Ethics Committee and informed consent, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The orbicularis oculi is more resistant to non-depolarizing agents than the adductor pollicis and direct facial muscle stimulation can occur unintentionally around the eye. 4 Alternative techniques, such as phonomyography, 15 have been proposed for monitoring NMB during cardiac surgery, …”
Section: Conclusion : Nous Devons éViter D'administrer De Fortes Dosementioning
confidence: 99%
“…The orbicularis oculi is more resistant to non-depolarizing agents than the adductor pollicis and direct facial muscle stimulation can occur unintentionally around the eye. 4 Alternative techniques, such as phonomyography, 15 have been proposed for monitoring NMB during cardiac surgery, …”
Section: Conclusion : Nous Devons éViter D'administrer De Fortes Dosementioning
confidence: 99%
“…It has been shown that the peak frequency of a typical signal is at 4-5 Hz and the maximum power occurs over a spectrum of frequencies up to 50 Hz. 42 Good to very good agreement with MMG or MMGlike methods has been shown for the adducting laryngeal muscles, 50 the CS, 21 and the AP. 51 In fact, at the CS, PMG was more sensitive in detecting the peak effect in comparison with AMG.…”
Section: Phonomyographymentioning
confidence: 84%
“…21 These methods measure the actual force by indirect methods, such as the change of pressure exerted onto a balloon compressed by movement of the thumb or contraction of the CS. Again, these methods are not easy to apply in the clinical setting, and are reserved primarily for research purposes as a gold standard or reference against which other methods can be tested.…”
Section: Mechanomyography (Mmg)mentioning
confidence: 99%
“…Initially, this method was called acoustic myography and used an air-chamber interface between the skin and the microphone. 7,8 It shows good agreement for several muscles with the gold standard of monitoring, MMG, [9][10][11] and can be applied at any muscle of interest.…”
mentioning
confidence: 75%